Learning models for effective propagation of sustainable construction practices in the built environment / Samuel Ekung & Isaac Odesola - Ekung, Samuel; Odesola, Isaac (Universiti Teknologi MARA, Perak, 2018)
The drive to achieve sustainable built environment has made learning new skills relating to Sustainable Construction Practices (SCP) imperative. This study investigated whether learning method can improve uptake of SCP through knowledge enhancement. Using survey research strategy, data from 206 construction professionals in Nigeria were collected and analysed. The results revealed that Andragogy and Experiential learning models strongly correlated SCP transfer requirements, and are therefore, appropriate models to embed SCP within existing ethos in the built environment. The study espoused the critical roles of experience and hands-on-project as prerequisite reinforcements for effective learning of SCP.